Identifikasi Konstitusionalisme Iklim dalam Tata Hukum Indonesia - Failaq, Muhammad RM Fayasy; Pradana, Arsyad Surya; Arti, Rohmatin Dwi (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2024)
In efforts to combat climate change, many countries have embraced the concept of climate constitutionalism, directly embedding language related to climate and climate change into their constitutional texts. However, this approach remains familiar in Indonesia, where constitutionalism traditionally emphasizes constraining government power through an institutionalist lens. Given the potential for climate constitutionalism to bolster climate change mitigation efforts through constitutional regulations and judicial interpretation, studying its applicability in Indonesia is crucial. This article seeks to explore and propose options for incorporating climate-related clauses into the Indonesian constitution. Employing normative juridical methods, data is gathered through literature reviews focused on this issue. The findings reveal that, currently, the Indonesian constitution needs more specific climate clauses despite explicit regulations addressing climate issues at the legal level. Challenges in integrating these provisions stem from constitutional structure, the intricacies of constitutional amendments, and a need for more momentum for amendments targeting climate change specifically. However, avenues exist for integrating climate clauses into the constitution, primarily by focusing on several key aspects. These include environmental rights, climate rights, future generations’ rights, articles about the nation’s economy, and provisions related to national territory and international agreements. In conclusion, while Indonesia’s constitution does not presently incorporate climate clauses, there are viable pathways for their integration. Such inclusion could significantly bolster the country’s efforts to address climate change and its impacts. AbstrakDalam rangka mitigasi perubahan iklim, berbagai negara telah mengadopsi konsep konstitusionalisme iklim dengan memasukkan diksi terkait iklim (perubahan iklim) dalam teks konstitusinya. Namun, konsep ini tampak asing di Indonesia. Hal ini disebabkan konstitusionalisme di Indonesia lebih berfokus pada pembatasan kekuasaan pemerintah melalui pendekatan institusionalis. Kajian konstitusionalisme iklim di Indonesia menjadi penting karena potensinya dalam meningkatkan upaya mitigasi perubahan iklim melalui regulasi turunan konstitusi dan interpretasi peradilan. Artikel ini bertujuan untuk mengidentifikasi dan menawarkan opsi-opsi yang memungkinkan integrasi klausul iklim ke dalam konstitusi Indonesia. Penelitian ini menggunakan metode yuridis normatif, dengan data yang diperoleh dari studi pustaka terkait dengan isu tersebut. Kesimpulan penelitian ini menunjukkan bahwa pertama, konstitusi Indonesia belum memiliki klausul iklim yang spesifik untuk mendukung kerangka konstitusionalisme iklim, walaupun pada tingkat undang-undang telah ada yang mengatur isu ini secara eksplisit. Kesulitan dalam mengakomodir ketentuan tersebut dikarenakan struktur UUD, corak perubahan konstitusi, serta kurangnya aspirasi amandemen yang spesifik terhadap isu perubahan iklim. Kedua, klausul iklim dapat diintegrasikan ke dalam konstitusi dengan fokus pada beberapa aspek, seperti hak atas lingkungan, hak iklim, hak generasi mendatang, pasal-pasal terkait perekonomian negara, serta melalui adopsi pada pasal yang berkaitan dengan wilayah negara dan perjanjian internasional.